Analysis of the environmental perception of teachers and students of Raimundo Nonato Sobrinho School in Paragominas City, Pará State, Brazil (Research, Society and Development, 2020)
Demographic growth, accompanied by technological advances and consumer habits, has increased the volume of solid urban waste generated by harmful impacts on the environment and on man. Among these residues, organic ones are the most produced daily and their use in the form of compost is one of the most promising alternatives, as it reduces the volume of them effectively. To this end, Environmental Education is seen as a way to make the population aware of more sustainable practices, such as waste reuse. Thus, this work seeks to analyze the perception and practices of environmental education of teachers and students of the 5th year in a school in Paragominas-PA. Data collection occurred through the application of questionnaires, which had open and closed questions, to 9 teachers and 47 students. The results indicated that the perception, both of teachers and students about the environment, was positive, however, there was a need to develop practical interventions in order to awaken students' socio-environmental responsibility. In view of this, composting was suggested as a way to reuse organic waste and to dispose of the compost generated in a vegetable garden at the institution itself, provided there was collaboration and encouragement from the school community.